Autobiographical tendency of Ramón Otero Pedrayo: Eladia Pedrayo Ansoar, mother and literary model (Nudos. Revista Transdisciplinar de Sociología, Teoría y Didáctica de la Literatura, 2018)
Eladia Pedrayo Ansoar, the mother of the writer Ramón Otero Pedrayo, serves as a model for two important female characters in his literary work, Mrs. María, in Arredor de si (1930) and Mrs. Ramona, in Os camiños da vida (1928).
Keywords: Ramón Otero Pedrayo, Eladia Pedrayo Ansoar, literary models, Circling, The ways of the life.